Dielectric composition and electronic component
By introducing Ba-Mg-Si-O segregated particles into the dielectric composition of electronic components, the crack problem caused by thermal shock is solved, and higher heat resistance and dielectric properties are achieved.
Patent Information
- Application Number
- CN202410898091.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-18
- Filing Date
- 2024-07-05
- Publication Date
- 2025-02-21
AI Technical Summary
Existing electronic components are prone to cracks in the case of thermal shock, etc., resulting in a degradation of the performance of the dielectric composition.
A dielectric composition containing Ba-Mg-Si-O segregated particles is employed which inhibits excessive grain growth of the main phase particles and reaches the segregated particles through the crack to stop the development of the crack.
Cracks generated by thermal shock or the like are effectively suppressed, and the heat resistance and relative dielectric constant of the dielectric composition are improved.
Smart Images

Figure CN119495510A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority based on Japanese Patent Application No. 2023-133537 filed on August 18, 2023, and the entirety of the disclosure is incorporated into this specification by reference.
[0002] The present invention relates to a dielectric composition and an electronic component including a dielectric layer composed of the dielectric composition. Background Art
[0003] Electronic components such as multilayer ceramic capacitors that utilize dielectric properties exhibited by dielectrics are mounted in electronic circuits or power supply circuits incorporated in electronic equipment. Patent document 1 (Japanese Patent Publication No. 2001-6966) discloses that the main component of dielectric ceramics of electronic components is a general formula of ABO 3 (wherein A is at least one of Ba, Sr, Ca and Mg, and B is at least one of Ti, Zr and Hf).
[0004] The conventional electronic components shown in Patent Document 1 are mounted on a circuit board or the like by a method such as "reflow soldering" or "flow soldering". Compared with "reflow soldering", "flow soldering" has the advantage of being inexpensive, but when mounting an electronic component on a substrate by "flow soldering", cracks may occur in a dielectric composition (dielectric ceramic) of the electronic component due to thermal shock or the like. Therefore, it is desired to develop a dielectric composition that can effectively prevent cracks caused by thermal shock or the like. Summary of the invention
[0005] Technical problem to be solved by the invention
[0006] The present invention has been made in view of such actual circumstances, and an object of the present invention is to provide a dielectric composition capable of suppressing cracks caused by thermal shock or the like.
[0007] Technical solutions for solving technical problems
[0008] In order to achieve the above object, the dielectric composition involved in the present invention is a dielectric composition comprising main phase particles and segregation particles, wherein:
[0009] At least a portion of the segregated particles are Ba-Mg-Si-O segregated particles containing Ba, Mg, Si and O.
[0010] When the total amount of the metal element and Si contained in the Ba-Mg-Si-O segregation particles is 100 parts by mole, the total amount of Ba, Mg and Si contained in the Ba-Mg-Si-O segregation particles is 70 parts by mole or more.
[0011] The present inventors have conducted intensive studies on a dielectric composition capable of suppressing cracks caused by thermal shock or the like, and as a result have found that a dielectric composition having Ba-Mg-Si-O segregated particles has an excellent effect on suppressing cracks, thereby completing the present invention.
[0012] It is considered that the reason why cracks caused by thermal shock or the like can be suppressed by the Ba-Mg-Si-O segregated particles is that, for example, the Ba-Mg-Si-O segregated particles suppress excessive grain growth of the main phase particles.
[0013] In addition, it is considered that even if cracks are generated in the dielectric composition, the cracks reach the Ba-Mg-Si-O segregation particles, thereby stopping the crack growth.
[0014] The Ba—Mg—Si—O segregation particles may exist at the grain boundaries of the main phase particles.
[0015] Preferably, the ratio of Mg in the Ba—Mg—Si—O segregated particles to the total of Mg and Si is 0.25 to 0.75.
[0016] Preferably, the average particle size of the Ba—Mg—Si—O segregated particles is 0.1 μm or less.
[0017] Preferably, when observing a total of 5 μm 2 When the cross section of the dielectric composition is observed, the Ba-Mg-Si-O segregated particles are observed to be 0.5 to 10 particles / μm on average. 2 .
[0018] By making the Ba-Mg-Si-O segregation particles finer and increasing the surface area, the surface energy can be increased. Therefore, even if only a small amount of Ba-Mg-Si-O segregation particles are included, the movement of the grain boundaries of the main phase particles can be effectively suppressed, and the excessive grain growth of the main phase particles can be further suppressed. As a result, cracks can be made less likely to occur.
[0019] In addition, since the number of Ba-Mg-Si-O segregated particles is small, the Ba-Mg-Si-O segregated particles do not completely block the main phase particles, so that heat conduction between the main phase particles is easy, and the thermal conductivity of the dielectric composition as a whole is also increased, and the thermal shock resistance is enhanced. As a result, cracks caused by thermal shock can be further suppressed.
[0020] Furthermore, when the average number of Ba-Mg-Si-O segregated particles is within the above range, a high relative dielectric constant can be maintained compared to a case where the average number of Ba-Mg-Si-O segregated particles is within the above range, it is believed that the main phase particles that mainly exert dielectric properties are sufficiently present in the dielectric composition, and therefore the relative dielectric constant becomes high.
[0021] Preferably, the composition of the main phase particles is BaTiO 3 .
[0022] Preferably, the composition of the Ba-Mg-Si-O segregation particles is Ba{Mg a Si (1-a)} 4 O 7 , said a is 0.25~0.75.
[0023] The electronic component of the present invention includes a dielectric layer containing the dielectric composition of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1A It is a cross-sectional view of a multilayer ceramic capacitor according to one embodiment of the present invention.
[0025] Figure 1B It is along Figure 1A A cross-sectional view of an IB-IB line stacked ceramic capacitor.
[0026] Figure 2 It is a schematic diagram of a cross section of a dielectric composition according to one embodiment of the present invention.
[0027] Figure 3 It is a schematic diagram of a cross section of a dielectric composition according to another embodiment of the present invention.
[0028] Explanation of symbols:
[0029] 1…Multilayer ceramic capacitor
[0030] 10…Component body
[0031] 2…Dielectric layer
[0032] 20…Main phase particles
[0033] 22…RE-Mg-Ti-O segregation particles
[0034] 24…Ba-Mg-Si-O segregation particles
[0035] 26…Ba-RE-Si-O segregation particles
[0036] 28…Grain boundary
[0037] 3…Internal electrode layer
[0038] 4…External electrode DETAILED DESCRIPTION
[0039] [First embodiment]
[0040] <Multilayer Ceramic Capacitors>
[0041] exist Figure 1A and Figure 1B 1 shows a laminated ceramic capacitor 1 as an example of an electronic component of the present embodiment. The laminated ceramic capacitor 1 has a component body 10 having a structure in which dielectric layers 2 and internal electrode layers 3 are alternately laminated. A pair of external electrodes 4 are formed at both ends of the component body 10, and the pair of external electrodes 4 are respectively connected to the internal electrode layers 3 alternately arranged inside the component body 10. The shape of the component body 10 is not particularly limited, and is usually set to a rectangular parallelepiped. In addition, the size of the component body 10 is not particularly limited, as long as it is set to an appropriate size according to the purpose.
[0042] In this embodiment, the longitudinal dimension L0 of the element body 10 (see Figure 1A ) is preferably 3.5 to 0.4 mm. In this embodiment, the width dimension W0 of the element body 10 (see Figure 1B ) is preferably 2.7 to 0.2 mm.
[0043] As specific dimensions of the element body 10, L0×W0 may be (3.2±0.3) mm×(2.5±0.2) mm, (3.2±0.3) mm×(1.6±0.2) mm, (2.0±0.2) mm×(1.2±0.1) mm, (1.6±0.2) mm×(0.8±0.1) mm, (1.0±0.1) mm×(0.5±0.05) mm, (0.6±0.06) mm×(0.3±0.03) mm, (0.4±0.04) mm×(0.2±0.02) mm, etc. In addition, H0 is not particularly limited, and may be, for example, equal to or less than W0.
[0044] The dielectric layer 2 is composed of a dielectric composition of the present embodiment described later.
[0045] The thickness of each layer of the dielectric layer 2 (interlayer thickness) is not particularly limited and can be arbitrarily set according to the desired characteristics and uses. Generally, the interlayer thickness is preferably 30 μm or less, more preferably 10 μm or less, and further preferably 5 μm or less. In addition, the number of stacked layers of the dielectric layer 2 is not particularly limited, but in the present embodiment, for example, it is preferably 20 or more.
[0046] In the present embodiment, the internal electrode layers 3 are stacked so that the respective end portions are alternately exposed on the surfaces of two opposing end faces of the element body 10 .
[0047] The thickness of the internal electrode layer 3 is not particularly limited, but is, for example, 2 μm or less, and preferably 1.5 μm or less.
[0048] There is no particular limitation on the conductive material contained in the internal electrode layer 3. Examples of the noble metal used as the conductive material include Pd, Pt, and Ag-Pd alloys. Examples of the base metal used as the conductive material include Ni, Ni alloys, Cu, and Cu alloys. In addition, various trace components such as P and / or S may be contained in Ni, Ni alloys, Cu, or Cu alloys in an amount of less than 0.1 mass %. In addition, the internal electrode layer 3 may also be formed using a commercially available electrode paste. The thickness of the internal electrode layer 3 may be appropriately determined according to the intended use, etc.
[0049] The conductive material contained in the external electrode 4 is not particularly limited. For example, a known conductive material such as Ni, Cu, Sn, Ag, Pd, Pt, Au or alloys thereof, conductive resin, etc. can be used. The thickness of the external electrode 4 can be appropriately determined according to the application, etc.
[0050] <Dielectric composition>
[0051] like Figure 2 As shown, the dielectric composition constituting the dielectric layer 2 includes main phase grains 20 and Ba-Mg-Si-O segregation grains 24. The Ba-Mg-Si-O segregation grains 24 contain Ba, Mg, Si, and O. The Ba-Mg-Si-O segregation grains 24 may also exist at the grain boundaries 28 of the main phase grains 20.
[0052] In the present embodiment, at least a part of the segregated particles may be the Ba—Mg—Si—O segregated particles 24 , and the dielectric composition may include segregated particles having a composition other than the Ba—Mg—Si—O segregated particles 24 .
[0053] <Main phase particles>
[0054] The main phase particles 20 of this embodiment contain AMO 3 The main component of the main phase particles 20 is a component that accounts for 80 to 100 parts by mass, preferably 90 to 100 parts by mass, based on 100 parts by mass of the main phase particles 20.
[0055] The molar ratio of the A element to the M element represented by (molar ratio of A / molar ratio of M) may be 1 or may not be 1. (molar ratio of A / molar ratio of M) is preferably 0.9 to 1.2.
[0056] When (the molar ratio of A / the molar ratio of M) is greater than 1, the Ba-Mg-Si-O segregation particles 24 and / or the Ba-RE-Si-O segregation particles 26 described later tend to be easily formed.
[0057] The element A contains at least one selected from Ba and Ca. The element A is preferably Ba. Thus, the dielectric composition can exhibit a higher relative dielectric constant.
[0058] When the element A is Ba and Ca, the content of Ba is preferably 0.9 to 1 part by mole, based on 1 part by mole of the total of Ba and Ca.
[0059] The M element contains at least one selected from Ti and Zr. The M element is preferably Ti. Thus, the dielectric composition can exhibit a higher relative dielectric constant.
[0060] When the M element is Ti and Zr, the content of Ti is preferably 0.8 to 1 part by mole, based on 1 part by mole of the total of Ti and Zr.
[0061] The main phase grains 20 may contain Mg, Mn, Cr, Si, rare earth elements (RE elements), V, Li, B, Al, and the like.
[0062] <Ba-Mg-Si-O segregation particles>
[0063] The Ba—Mg—Si—O segregation particles 24 contain Ba, Mg, Si, and O.
[0064] When the total amount of the metal element and Si contained in the Ba-Mg-Si-O segregation particles 24 is 100 parts by mole, the total amount of Ba, Mg, and Si contained in the Ba-Mg-Si-O segregation particles 24 is 70 parts by mole or more.
[0065] The ratio of Mg to the total of Mg and Si in the Ba—Mg—Si—O segregated particles 24 is 0.25 to 0.75, preferably 0.27 to 0.73.
[0066] The ratio of Ba in the Ba-Mg-Si-O segregation particles 24 to the total of Ba, Mg, and Si is preferably 0.15 or more.
[0067] The composition of the Ba-Mg-Si-O segregation particles 24 is not particularly limited. For example, it may be Ba{Mg a Si (1-a)} 4 O 7 , a can be 0.25~0.75, or BaMg 2 Si 2O 7 .
[0068] The average particle size of the Ba—Mg—Si—O segregated particles 24 is preferably 0.1 μm or less, and more preferably 0.05 μm or less.
[0069] A total of 5 μm was observed 2 When the cross section of the dielectric composition is observed, it is preferable that the number of Ba-Mg-Si-O segregation particles 24 observed is 0.5 to 10 / μm on average. 2 More preferably, 0.6 to 9.2 pieces / μm are observed 2 Here, for "when a total of 5 μm is observed 2 When the cross section of the dielectric composition is observed, the observation field is 1 field, which means "observation of 5 μm 2 When the observation field is two or more, it means "the total area of each field of view is 5 μm 2 In the above cases, when observing in each field of view, it is preferred to observe in each field of view. 2 Observation within the scope of .
[0070] In addition, for the Ba-Mg-Si-O segregation particles 24, all the segregation particles included in one field of view were counted as 1. For example, the Ba-Mg-Si-O segregation particles 24 observed at one end of the field of view and partially missing were not counted.
[0071] The crystal system of the Ba—Mg—Si—O segregation particles 24 is preferably a monoclinic system.
[0072] The space group of the Ba—Mg—Si—O segregation particles 24 is preferably C2 / c.
[0073] <Method for Confirming Segregated Particles>
[0074] In the present embodiment, the method for determining whether or not the dielectric composition constituting the dielectric layer 2 has the Ba—Mg—Si—O segregated particles 24 is not particularly limited, and a specific method is exemplified below.
[0075] First, a cross section of the dielectric composition is photographed using a scanning transmission electron microscope (STEM) to obtain a dark field (DF) image. The width of the photographed field of view is not particularly limited, and is, for example, about 1 to 10 μm square. The region having a contrast different from that of the main phase particles 20 in the dark field image is identified as a heterogeneous phase. Whether there is a different contrast, that is, whether there is a heterogeneous phase, can be determined by visual observation or by software for image processing.
[0076] Then, various elements were measured for the above-mentioned heterogeneous phase by energy dispersive X-ray analysis (EDS analysis).
[0077] Ba, Mg, Si and O exist at the same position of the heterophase. When the total amount of the metal elements and Si in the heterophase is set to 100 mol parts, if the total amount of Ba, Mg and Si in the heterophase is 70 mol parts or more, the heterophase can be judged to be a Ba-Mg-Si-O segregation particle 24.
[0078] In addition, it can be determined that the particles are Ba—Mg—Si—O segregation particles 24 from the element mapping image.
[0079] <Method for manufacturing multilayer ceramic capacitor>
[0080] Next, the following description Figure 1A and Figure 1B An example of a method for manufacturing the multilayer ceramic capacitor 1 is shown.
[0081] In this embodiment, AMO, which is the main component of the main phase particles 20 constituting the above-mentioned dielectric composition, is prepared. 3 and a calcined powder of a raw material mixture of the Ba—Mg—Si—O segregation particles 24.
[0082] AMO 3 The calcined powder is a calcined powder of the A element and the M element which constitute the main phase particles 20 after sintering.
[0083] The calcined powder of the raw material mixture of the Ba—Mg—Si—O segregation particles 24 is a calcined powder of Ba, Mg, and Si that constitutes the Ba—Mg—Si—O segregation particles 24 after firing.
[0084] As the raw material of each element mentioned above, there is no particular limitation, and the oxide of each element can be used. In addition, various compounds that can obtain the oxide of each element by calcination can be used. As various compounds, examples such as carbonates, oxalates, nitrates, hydroxides, organometallic compounds, etc. can be exemplified. In the present embodiment, the above-mentioned starting raw material is preferably a powder.
[0085] Weigh the AMO in the prepared starting material according to the specified ratio 3 After the raw materials are pelletized, wet mixing is performed for a predetermined time using a ball mill or the like. After the mixed powder is dried, heat treatment is performed in the air at a temperature of 700 to 1300°C to obtain AMO 3 The calcined powder of the raw material mixture of the particles. Alternatively, the calcined powder may be pulverized for a predetermined time using a ball mill or the like.
[0086] Various compounds such as oxides of the elements that constitute the Ba-Mg-Si-O segregation particles 24 after firing are prepared, and after heat treatment, they are pulverized for a predetermined time using a ball mill or the like to obtain a calcined powder of the raw material mixture of the Ba-Mg-Si-O segregation particles 24.
[0087] For example, by changing the pulverization time, the particle size of the Ba-Mg-Si-O segregation particles 24 can be changed. The longer the pulverization time, the smaller the particle size of the Ba-Mg-Si-O segregation particles 24. In addition, by changing the media diameter of the ball mill, the particle size of the Ba-Mg-Si-O segregation particles 24 can also be changed.
[0088] Next, a paste for making green chips is prepared. 3 The calcined powder of the raw material mixture of particles, the calcined powder of the raw material mixture of Ba-Mg-Si-O segregated particles 24, a binder, and a solvent are kneaded and coated to prepare a dielectric layer paste. The binder and the solvent may be known materials.
[0089] The dielectric layer paste may contain additives such as a plasticizer and a dispersant as necessary.
[0090] The internal electrode layer paste is obtained by kneading the above-mentioned conductive material raw materials, a binder, and a solvent. The binder and the solvent may be known materials. The internal electrode layer paste may also contain additives such as general materials or plasticizers as needed.
[0091] The external electrode paste can be prepared in the same manner as the internal electrode layer paste.
[0092] Green sheets are formed using the obtained pastes, internal electrode patterns are formed on the green sheets, and a laminated body is obtained by laminating these sheets. Next, the laminated body is cut to obtain green chips.
[0093] The obtained green chip is subjected to a binder removal treatment as necessary. The binder removal treatment conditions are preferably set at a holding temperature of 200 to 350°C, for example.
[0094] After the binder removal treatment, the green chip is fired to obtain the element body 10. In this embodiment, the atmosphere during firing is not particularly limited, and it can be in air or in a reducing atmosphere. In this embodiment, the holding temperature during firing is not particularly limited, and is, for example, 1200 to 1350°C.
[0095] After firing, the obtained element body 10 is subjected to reoxidation treatment (annealing) as necessary. For example, the annealing conditions preferably set the oxygen partial pressure during annealing to be higher than the oxygen partial pressure during firing and set the holding temperature to be 1150° C. or lower.
[0096] The dielectric composition constituting the dielectric layer 2 of the element body 10 obtained as described above is the above-mentioned dielectric composition. The element body 10 is subjected to end surface grinding, and an external electrode paste is applied and sintered to form the external electrode 4. Then, if necessary, a coating layer is formed on the surface of the external electrode 4 by plating or the like.
[0097] In this manner, the multilayer ceramic capacitor 1 of the present embodiment is manufactured.
[0098] <Summary of the First Embodiment>
[0099] One of the causes of cracks in the dielectric composition is "excessive grain growth of the main phase particles 20". That is, due to the excessive grain growth of the main phase particles 20, pores are easily generated in the dielectric composition, and heat shock is applied by "flow welding" or the like, thereby sometimes causing cracks to be generated starting from the pores.
[0100] Therefore, in order to suppress cracking of the dielectric composition, it is desirable to suppress excessive grain growth of the main phase particles 20 .
[0101] As one method of suppressing excessive grain growth of the main phase particles 20, a method of using the "pinning effect by the second phase particles" can be cited. Here, the "pinning effect" is a phenomenon in which the movement of the grain boundaries 28 is suppressed by the second phase particles, thereby suppressing the grain growth of the first phase particles (the main phase particles 20 in this embodiment). Therefore, the present inventors have studied a method of making particles that become second phase particles exist in the dielectric composition.
[0102] First, when the AMO particles 20 that become the main phase 3 Adding SiO 2 When sintered, SiO 2 With AMO 3 Reaction, AMO 3 The composition of the main phase particles 20 may change, and sometimes the main phase particles 20 may undergo excessive grain growth.
[0103] In addition, when MgO is a single substance, it is easily dissolved in AMO. 3 , therefore, sometimes dissolves in AMO 3 Therefore, it is difficult for MgO to exist as second phase particles that exert a pinning effect in the dielectric composition.
[0104] Furthermore, SiO 2 Compounds of MgO and AMO 3 Therefore, SiO 2 It is also difficult for the compound of MgO to exist as second phase particles that exert a pinning effect in the dielectric composition.
[0105] Therefore, the inventors found that BaO, SiO2 The Ba-Mg-Si-O segregation particles 24 are formed by the formation of Ba-Mg-Si-O and MgO, and become the second phase particles. The Ba-Mg-Si-O segregation particles 24 are stable compounds, and therefore, it is considered that they are not easily soluble in the AMO 3 The main phase grains 20 are mainly composed of Ba-Mg-Si-O. Therefore, the presence of the Ba-Mg-Si-O segregation grains 24 at the grain boundaries 28 of the main phase grains 20 can effectively suppress the movement of the grain boundaries 28 of the main phase grains 20 by the pinning effect, and can suppress the grain growth of the main phase grains 20. As a result, cracks caused by thermal shock or the like can be less likely to occur.
[0106] Furthermore, even if cracks are generated in the dielectric composition, the cracks can reach the Ba—Mg—Si—O segregation particles 24 and stop the cracks from growing. In other words, the Ba—Mg—Si—O segregation particles 24 can stop the cracks from growing.
[0107] Furthermore, by making the Ba-Mg-Si-O segregation particles 24 finer and increasing the surface area, the surface energy can be increased. Therefore, even if only a small amount is included between the main phase particles 20, the movement of the grain boundaries 28 of the main phase particles 22 can be effectively suppressed, the grain growth of the main phase particles 20 can be suppressed, cracks are less likely to occur, and the development of cracks can be stopped by the Ba-Mg-Si-O segregation particles 24.
[0108] Furthermore, when there are a small number of Ba-Mg-Si-O segregation particles 24, the main phase particles 20 are not completely blocked, so that heat conduction is easily performed between the main phase particles 20, and the thermal conductivity of the dielectric composition as a whole is also increased, and the thermal shock resistance is enhanced. As a result, cracks caused by thermal shock can be further suppressed.
[0109] [Second embodiment]
[0110] like Figure 3 As shown, the dielectric composition constituting the dielectric layer 2 of the present embodiment includes RE-Mg-Ti-O segregation particles 22 and Ba-RE-Si-O segregation particles 26 in addition to the main phase particles 20 and the Ba-Mg-Si-O segregation particles 24 .
[0111] The RE-Mg-Ti-O segregation grains 22 and / or the Ba-RE-Si-O segregation grains 26 may be present at the grain boundaries 28 of the main phase grains 20 .
[0112] Furthermore, the Ba-Mg-Si-O segregation particles 24 can be made finer than the RE-Mg-Ti-O segregation particles 22. Therefore, in the case of the Ba-Mg-Si-O segregation particles 24, heat conduction between the main phase particles 20 is easier than in the case of the RE-Mg-Ti-O segregation particles 22, and the thermal conductivity of the dielectric composition as a whole becomes higher, and there is a tendency to have a stronger resistance to thermal shock. As a result, cracks caused by thermal shock tend to be further suppressed.
[0113] <RE-Mg-Ti-O segregation particles>
[0114] The RE-Mg-Ti-O segregation particles 22 contain RE elements, Mg, Ti, and O.
[0115] "RE element" means a rare earth element. The type of RE element is not particularly limited, and for example, Y, Dy, or Ho can be used. The RE element may be used alone or in combination of two or more.
[0116] When the total amount of the metal element and Si contained in the RE-Mg-Ti-O segregation particles 22 is 100 parts by mole, the total amount of the RE element, Mg, and Ti contained in the RE-Mg-Ti-O segregation particles 22 is preferably 70 parts by mole or more.
[0117] The ratio of Mg in the RE-Mg-Ti-O segregated particles 22 to the total of the RE element and Mg is 0.1 to 0.3.
[0118] The ratio of Ti to the total of the RE element and Mg in the RE-Mg-Ti-O segregated particles 22 is preferably 0.7 to 1.3.
[0119] The composition of the RE-Mg-Ti-O segregation particles 22 is not particularly limited, and may be, for example, {RE (1-a) Mg a} 2 Ti 2 O 7-a , a can also be 0.1~0.3.
[0120] The average particle size of the RE-Mg-Ti-O segregated particles 22 is preferably 0.1 μm or less, and more preferably 0.05 μm or less. The average particle size of the RE-Mg-Ti-O segregated particles 22 may be an average of the equivalent circle diameters of the RE-Mg-Ti-O segregated particles 22 .
[0121] After observing a total of 5μm 2 When the cross section of the dielectric composition is observed, it is preferred that an average of 0.2 to 2 / μm 2More preferably, 0.5 to 1.5 particles / μm are observed. 2 .
[0122] In addition, for the RE-Mg-Ti-O segregated particles 22, all the segregated particles included in one field of view were counted as 1. For example, the RE-Mg-Ti-O segregated particles 22 observed at one end of the field of view and partially missing were not counted.
[0123] The crystal system of the RE-Mg-Ti-O segregated particles 22 is preferably a cubic system.
[0124] The space group of the RE-Mg-Ti-O segregation particles 22 is preferably
[0125] <Ba-RE-Si-O segregation particles>
[0126] The Ba—RE—Si—O segregation grains 26 contain Ba, RE element, Si, and O.
[0127] When the total amount of the metal element and Si contained in the Ba-RE-Si-O segregation particles 26 is 100 parts by mole, the total amount of Ba, RE elements and Si in the Ba-RE-Si-O segregation particles 26 is preferably 97 parts by mole or more. Thus, the dielectric composition can exhibit high density and high resistivity.
[0128] The ratio of Ba to the total of Ba, RE, and Si in the Ba-RE-Si-O segregation particles 26 is preferably 0.10 to 0.25. This allows the dielectric composition to exhibit high density and high resistivity.
[0129] The ratio of RE to the total of Ba, RE, and Si in the Ba-RE-Si-O segregation particles 26 is preferably 0.33 to 0.59. This allows the dielectric composition to exhibit high density and high resistivity.
[0130] The ratio of Si to the total of Ba, RE, and Si in the Ba-RE-Si-O segregation particles 26 is preferably 0.16 to 0.50. This allows the dielectric composition to exhibit high density and high resistivity.
[0131] The crystal system of the Ba-RE-Si-O segregation particles 26 is preferably tetragonal. Thus, the dielectric composition can exhibit a higher density and a higher resistivity.
[0132] The space group of the Ba-RE-Si-O segregation particles 26 is preferably Thus, the dielectric composition of the present embodiment can exhibit higher density and higher resistivity.
[0133] The composition of the Ba-RE-Si-O segregation particles 26 is not particularly limited. For example, Ba 5 RE 13 Si 8 O 41 In more detail, we can cite Ba 5 Y 13 Si 8 O 41 , Ba 5 Dy 13 Si 8 O 41 , Ba 5 Ho 13 Si 8 O 41 .
[0134] <Method for Confirming Segregated Particles>
[0135] The method for determining whether the dielectric composition constituting the dielectric layer 2 has RE-Mg-Ti-O segregation particles 22 or Ba-RE-Si-O segregation particles 26 is not particularly limited, and can be determined by the same method as the method for determining whether the dielectric composition constituting the dielectric layer 2 has Ba-Mg-Si-O segregation particles 24 described in the first embodiment.
[0136] That is, when RE elements, Mg, Ti and O exist at the same position of the heterophase, and when the total of the metal elements and Si in the heterophase is set to 100 mol parts, the total of the RE elements, Mg and Ti in the heterophase is more than 70 mol parts, and Mg / (RE+Mg) in the heterophase is 0.1 to 0.3, the heterophase can be judged to be RE-Mg-Ti-O segregation particles 22.
[0137] Similarly, when Ba, RE, Si and O exist at the same position of a heterophase, and the total of the metal elements and Si in the heterophase is set to 100 mol parts, if the total of Ba, RE and Si in the heterophase is greater than 97 mol parts, the heterophase can be judged to be a Ba-RE-Si-O segregation particle 26.
[0138] In addition, it can be determined that it is the RE-Mg-Ti-O segregation particle 22 or the Ba-RE-Si-O segregation particle 26 by the element mapping image.
[0139] The method for manufacturing the multilayer ceramic capacitor of the present embodiment is not particularly limited, and can be the same method as the method for manufacturing the multilayer ceramic capacitor described in the first embodiment.
[0140] Specifically, in this embodiment, in addition to preparing AMO, which is the main component of the main phase particles 20 constituting the dielectric composition, 3In addition to the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregation particles 22 and the calcined powder of the raw material mixture of the Ba-RE-Si-O segregation particles 26, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregation particles 22 and the calcined powder of the raw material mixture of the Ba-RE-Si-O segregation particles 26 are also prepared.
[0141] The calcined powder of the raw material mixture of the RE-Mg-Ti-O segregated particles 22 is a calcined powder of the RE element, Mg, and Ti that constitute the RE-Mg-Ti-O segregated particles 22 after firing.
[0142] The calcined powder of the raw material mixture of the Ba—RE—Si—O segregation particles 26 is a calcined powder of Ba, RE element, and Si which constitute the Ba—RE—Si—O segregation particles 26 after firing.
[0143] Various compounds such as oxides of the elements constituting the RE-Mg-Ti-O segregated particles 22 after firing are prepared, and after heat treatment, they are pulverized for a predetermined time using a ball mill or the like to obtain a calcined powder of a raw material mixture of the RE-Mg-Ti-O segregated particles 22 .
[0144] Similarly, various compounds such as oxides of the elements that constitute the Ba-RE-Si-O segregation particles 26 after firing are prepared, and after heat treatment, they are pulverized for a specified time using a ball mill or the like to obtain a calcined powder of the raw material mixture of the Ba-RE-Si-O segregation particles 26.
[0145] Next, a paste for making green chips is prepared. 3 The calcined powder of the raw material mixture of the particles, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregation particles 22, the calcined powder of the raw material mixture of the Ba-Mg-Si-O segregation particles 24, the calcined powder of the raw material mixture of the Ba-RE-Si-O segregation particles 26, a binder, and a solvent are kneaded and coated to prepare a dielectric layer paste. The binder and the solvent may be known materials.
[0146] The multilayer ceramic capacitor 1 of the present embodiment can be manufactured by using the same method as that of the first embodiment except for the above.
[0147] As mentioned above, although embodiment of this invention is described, this invention is not limited to the said embodiment at all, It can also change in various aspects within the scope of this invention.
[0148] For example, in the above-mentioned embodiment, the electronic component of the present invention is described as a laminated ceramic capacitor. However, the electronic component of the present invention is not limited to a laminated ceramic capacitor, and any electronic component may be used as long as it has the above-mentioned dielectric composition.
[0149] For example, a single-plate type ceramic capacitor in which a pair of electrodes are formed in the above-mentioned dielectric composition may be used.
[0150] In the second embodiment, the dielectric composition constituting the dielectric layer 2 includes the RE-Mg-Ti-O segregation particles 22 and the Ba-RE-Si-O segregation particles 26 in addition to the main phase particles 20 and the Ba-Mg-Si-O segregation particles 24. The RE-Mg-Ti-O segregation particles 22 and the Ba-RE-Si-O segregation particles 26 may not be included, or may include either one of them.
[0151] Example
[0152] Hereinafter, the present invention will be described in more detail using Examples and Comparative Examples. However, the present invention is not limited to the following Examples.
[0153] [Experiment 1]
[0154] As a starting material of the main phase particles 20 contained in the dielectric composition, BaCO was prepared. 3 、CaCO 3 、ZrO 2 、TiO 2 The prepared starting materials are weighed so that the main components of the main phase particles 20 after sintering are as shown in Table 1, Table 3, Table 5, Table 7 and Table 9.
[0155] Next, the weighed powders were wet mixed for 16 hours using ion exchange water as a dispersion medium using a ball mill, and the mixture was dried to obtain a mixed raw material powder. Then, the obtained mixed raw material powder was heat treated in the air at a temperature of 1000° C. for 2 hours, and wet pulverized for 16 hours using ion exchange water as a dispersion medium using a ball mill, and the mixture was dried to obtain a calcined powder of the raw material mixture of the main phase particles 20.
[0156] In addition, as a raw material of the Ba-Mg-Si-O segregation particles 24, BaCO 3 MgCO 3 、SiO 2 The prepared powder was weighed so that the "Mg / (Mg+Si)" and "Ba / (Ba+Mg+Si)" of the Ba-Mg-Si-O segregation particles 24 were as shown in Tables 1, 3, 5, 7 and 9.
[0157] Next, using ion exchange water as a dispersion medium, the weighed powders are wet-mixed for 16 hours in a ball mill, the mixture is dried, and heat-treated in the atmosphere at a temperature of 1000°C for 2 hours. Using ion exchange water as a dispersion medium, the powders are wet-milled for 16 hours in a ball mill, and the mixture is dried to obtain a calcined powder of the raw material mixture of Ba-Mg-Si-O segregation particles 24.
[0158] Furthermore, an inorganic additive was prepared by the following method. First, MgCO 3 , Y 2 O 3 、MnCO 3 and V 2 O 5 The powders of the above-mentioned compounds were wet mixed for 16 hours to obtain a mixture. The mixture was then dried and heat treated in the atmosphere at a temperature of 900° C. for 2 hours. The heat-treated mixture was wet ground in a ball mill using ion exchange water as a dispersion medium for 16 hours and dried to obtain an inorganic additive.
[0159] Next, the calcined powder of the raw material mixture of the main phase particles 20, the calcined powder of the raw material mixture of the Ba-Mg-Si-O segregation particles 24, the inorganic additive, the binder, and the solvent are kneaded and coated to prepare a dielectric layer paste. Here, the prepared starting materials are weighed so that the addition amount (unit: mass part) of the calcined powder of the raw material mixture of the Ba-Mg-Si-O segregation particles 24 is as described in Tables 1, 3, 5, 7, and 9 relative to 100 parts by mass of the calcined powder of the raw material mixture of the main phase particles 20 (recorded as "addition amount" in Tables 1, 3, 5, 7, and 9).
[0160] 56 parts by mass of nickel particles, 40 parts by mass of terpineol, 4 parts by mass of ethyl cellulose (molecular weight: 140,000), and 1 part by mass of benzotriazole were kneaded and paste-formed using a triple roll to prepare an internal electrode layer paste.
[0161] Then, the dielectric layer paste prepared in the above manner was used to form a green sheet on a PET film, and the internal electrode layer paste was screen-printed to form a green sheet.
[0162] A plurality of green sheets are stacked and bonded under pressure to produce a green stack, and the green stack is cut into a predetermined size to obtain a green chip.
[0163] The obtained green chip was subjected to a binder removal treatment, fired in a reducing atmosphere, and further subjected to an annealing treatment to obtain the element body 10. As for the firing conditions, the heating rate was set to 200°C / h, the holding temperature was set to 1250°C, and the holding time was set to 2 hours. The atmosphere gas was set to a mixed gas of nitrogen and hydrogen (hydrogen concentration 3%) humidified to a dew point of 20°C. In addition, as for the annealing treatment conditions, the holding temperature was set to 1050°C, and the holding time was set to 2 hours. The atmosphere gas was set to nitrogen humidified to a dew point of 20°C.
[0164] The element body 10 obtained as described above is subjected to end surface grinding, and an external electrode paste is applied and fired to form the external electrodes 4 .
[0165] In this manner, a multilayer ceramic capacitor 1 (hereinafter referred to as a “capacitor sample”) was obtained.
[0166] <Observation of main phase particles>
[0167] In the 1.7 μm×1.7 μm field of view of the cross section of the dielectric composition of the obtained capacitor sample, the main phase grains 20 were identified by STEM, and the main components of the main phase grains 20 were identified by EDS. The results are shown in Tables 1, 3, 5, 7, and 9.
[0168] <Observation of segregated particles>
[0169] In a 1.7 μm×1.7 μm field of view of a cross section of the dielectric composition of the obtained capacitor sample, heterogeneous phases were identified by STEM, and the amounts of Ba, Mg, Si, RE, and Ti were measured using EDS.
[0170] Ba, Mg and Si exist at the same position, and when the total of the metal elements and Si contained in the hetero phase is 100 parts by mole, if the total of Ba, Mg and Si is 70 parts by mole or more, the hetero phase is judged to be Ba-Mg-Si-O segregation particles 24. The results of the presence or absence of Ba-Mg-Si-O segregation particles 24, Mg / (Mg+Si) and Ba / (Ba+Mg+Si) are shown in Tables 1, 3, 5, 7 and 9. In addition, in each capacitor sample having Ba-Mg-Si-O segregation particles 24, it was confirmed that the Ba-Mg-Si-O segregation particles 24 existed at the grain boundaries 28 of the main phase particles 20.
[0171] <Crystal system>
[0172] The crystal system was analyzed by performing electron beam diffraction on the Ba-Mg-Si-O segregation particles 24 of the capacitor sample and analyzing the electron beam diffraction pattern. The results are shown in Tables 1, 3, 5, 7, and 9.
[0173] <320℃ thermal shock test>
[0174] After the capacitor sample was immersed in the flux, it was held with tweezers and immersed in a solder bath heated to 320°C. Then, after taking out the capacitor sample, it was ultrasonically cleaned with a diluent and its appearance was observed. This test was performed on 20 capacitor samples. The number of capacitor samples with cracks is shown in Tables 2, 4, 6, 8 and 10.
[0175] <Average particle size>
[0176] The average particle size was measured for each sample in Table 8 and Table 10. Specifically, the total particle size of 5 μm was observed. 2 The cross-section of the above dielectric composition was measured, and the circle equivalent diameter of the observed Ba-Mg-Si-O segregated particles 24 was measured, and the measured values were averaged to be the average particle size of the Ba-Mg-Si-O segregated particles 24. The results are shown in Tables 8 and 10.
[0177] <350℃ thermal shock test>
[0178] A 350°C heat shock test was performed on each sample in Table 4, Table 6, Table 8, and Table 10. Specifically, after the capacitor sample was immersed in flux, it was dipped in a solder tank heated to 350°C by pinching the capacitor sample with tweezers. Then, after taking out the capacitor sample, it was ultrasonically cleaned with a diluent, and then the appearance was observed. This test was performed on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Table 4, Table 6, Table 8, and Table 10.
[0179] <380℃ thermal shock test>
[0180] A 380°C heat shock test was performed on each sample in Table 8. Specifically, after the capacitor sample was immersed in flux, it was dipped in a solder bath heated to 380°C by pinching the capacitor sample with tweezers. Then, after taking out the capacitor sample, it was ultrasonically cleaned with a diluent and the appearance was observed. This test was performed on 20 capacitor samples. The number of capacitor samples that had cracks is shown in Table 8.
[0181] <Average number of particles>
[0182] The average number of particles was measured for each sample in Table 10. Specifically, the average number of particles was measured when observing a total of 5 μm 2 When the cross section of the above dielectric composition was observed, the average number of Ba-Mg-Si-O segregation particles 24 was calculated. The results are shown in Table 10.
[0183] <Relative dielectric constant>
[0184] In each sample in Table 10, the relative dielectric constant was measured. Specifically, at room temperature (20°C), a digital LCR meter (4284A manufactured by YHP Co.) was used to input a signal with a frequency of 1kHz and an input signal level (measurement voltage) of 1Vrms to the capacitor sample, and the electrostatic capacitance C was measured. Then, the relative dielectric constant was calculated based on the thickness of the dielectric layer, the overlapping area of the internal electrodes, the number of stacking layers, and the electrostatic capacitance C obtained from the measurement results. The results are shown in Table 10.
[0185] [Experiment 2]
[0186] In Experiment 2, the same method as Experiment 1 was used to prepare a dielectric layer paste, except that the calcined powder of the raw material mixture of the main phase particles 20, the calcined powder of the raw material mixture of the Ba-Mg-Si-O segregation particles 24, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregation particles 22 (RE element is Y), the inorganic additive, the binder, and the solvent were kneaded and coated to prepare the dielectric layer paste. The results of Experiment 2 are shown in Tables 11 to 13 as Sample No. 51.
[0187] The presence or absence of the Ba-Mg-Si-O segregation particles 24 was determined by the above method, and as a result, it was confirmed that the sample number 51 had the Ba-Mg-Si-O segregation particles 24 present in the grain boundaries 28 of the main phase particles 20. The results of measuring Mg / (Mg+Si) and Ba / (Ba+Mg+Si) for the sample number 51 by the above method are shown in Table 11.
[0188] The presence or absence of RE-Mg-Ti-O segregation particles 22 was determined by the method of the second embodiment described above, and as a result, it was confirmed that sample number 51 had RE-Mg-Ti-O segregation particles 22 present in the grain boundaries 28 of the main phase particles 20. The results of measuring Ti / (RE+Mg) and Mg / (RE+Mg) for sample number 51 are shown in Table 12.
[0189] In sample No. 51, the average number of particles of each segregated particle was determined by the above method, and a 320°C heat shock test was performed. A 24-hour PCT (pressure cooker test), a 240-hour PCT, and a 500-hour PCT were performed by the following method.
[0190] <24-hour PCT>
[0191] The capacitor samples were mounted on a FR4 substrate (glass epoxy substrate) using Sn-Ag-Cu solder, placed in a pressure cooker tank, and subjected to an accelerated humidity test for 24 hours at 121°C and 95% humidity. The test was performed on 80 capacitor samples. The number of defective capacitor samples is shown in Table 13.
[0192] <240 hours PCT>
[0193] The capacitor samples were mounted on a FR4 substrate (glass epoxy substrate) using Sn-Ag-Cu solder, placed in a pressure cooker tank, and subjected to an accelerated humidity test for 240 hours at 121°C and 95% humidity. The test was performed on 80 capacitor samples. The number of defective capacitor samples is shown in Table 13.
[0194] <500 hours PCT>
[0195] The capacitor samples were mounted on a FR4 substrate (glass epoxy substrate) using Sn-Ag-Cu solder, placed in a pressure cooker tank, and subjected to an accelerated humidity test for 500 hours at 121°C and 95% humidity. The test was performed on 80 capacitor samples. The number of defective capacitor samples is shown in Table 13.
[0196] [Experiment 3]
[0197] In Experiment 3, the same method as Experiment 1 was used except that the calcined powder of the raw material mixture of the main phase particles 20, the calcined powder of the raw material mixture of the Ba-Mg-Si-O segregation particles 24, the calcined powder of the raw material mixture of the Ba-RE-Si-O segregation particles 26 (RE element is Y), the inorganic additive, the binder, and the solvent were kneaded and coated to prepare a dielectric layer paste, and capacitor samples were obtained and evaluated in the same way as Experiment 2. The results of Experiment 3 are shown as Sample No. 52 in Tables 11 to 13.
[0198] The presence or absence of the Ba-Mg-Si-O segregation particles 24 was determined by the above method, and as a result, it was confirmed that sample number 52 had Ba-Mg-Si-O segregation particles 24 present in the grain boundaries 28 of the main phase particles 20. The results of measuring Mg / (Mg+Si) and Ba / (Ba+Mg+Si) for sample number 52 by the above method are shown in Table 11.
[0199] The presence or absence of the Ba-RE-Si-O segregation particles 26 was determined by the method of the second embodiment described above, and as a result, it was confirmed that sample number 52 had Ba-RE-Si-O segregation particles 26 present in the grain boundaries 28 of the main phase particles 20. The results of measuring Ba / (Ba+RE+Si) and RE / (Ba+RE+Si) for sample number 52 are shown in Table 12.
[0200] [Experiment 4]
[0201] In Experiment 4, the same method as Experiment 1 was used except that the calcined powder of the raw material mixture of the main phase particles 20, the calcined powder of the raw material mixture of the Ba-Mg-Si-O segregation particles 24, the calcined powder of the raw material mixture of the RE-Mg-Ti-O segregation particles 22 (RE element is Y), the calcined powder of the raw material mixture of the Ba-RE-Si-O segregation particles (RE element is Y), the inorganic additive, the binder, and the solvent were kneaded and coated to prepare a dielectric layer paste, and capacitor samples were obtained and evaluated in the same way as Experiment 2. The results of Experiment 4 are shown as Sample No. 53 in Tables 11 to 13.
[0202] The presence or absence of the Ba-Mg-Si-O segregation particles 24 was determined by the above method, and as a result, it was confirmed that sample number 53 had Ba-Mg-Si-O segregation particles 24 present in the grain boundaries 28 of the main phase particles 20. The results of measuring Mg / (Mg+Si) and Ba / (Ba+Mg+Si) for sample number 53 by the above method are shown in Table 11.
[0203] The presence or absence of RE-Mg-Ti-O segregation particles 22 was determined by the method of the second embodiment described above, and as a result, it was confirmed that sample number 53 had RE-Mg-Ti-O segregation particles 22 present in the grain boundaries 28 of the main phase particles 20. The results of measuring Ti / (RE+Mg) and Mg / (RE+Mg) for sample number 53 are shown in Table 12.
[0204] The presence or absence of the Ba-RE-Si-O segregation particles 26 was determined by the method of the second embodiment described above, and as a result, it was confirmed that sample number 53 had Ba-RE-Si-O segregation particles 26 present in the grain boundaries 28 of the main phase particles 20. The results of measuring Ba / (Ba+RE+Si) and RE / (Ba+RE+Si) for sample number 53 are shown in Table 12.
[0205] [Table 1]
[0206]
[0207] [Table 2]
[0208] Sample No. 320℃ thermal shock test 1 5 / 20 2 3 / 20 3 2 / 20 4 0 / 20 5 0 / 20 6 0 / 20
[0209] [Table 3]
[0210]
[0211] [Table 4]
[0212] Sample No. 320℃ thermal shock test 350℃ thermal shock test 11 2 / 20 - 12 0 / 20 2 / 20 13 0 / 20 0 / 20 4 0 / 20 0 / 20 14 0 / 20 0 / 20 15 0 / 20 2 / 20
[0213] [Table 5]
[0214]
[0215] [Table 6]
[0216] Sample No. 320℃ thermal shock test 350℃ thermal shock test 21 0 / 20 1 / 20 22 0 / 20 0 / 20 4 0 / 20 0 / 20
[0217] [Table 7]
[0218]
[0219] [Table 8]
[0220] Sample No. Average particle size [μm] 320℃ thermal shock test 350℃ thermal shock test 380℃ thermal shock test 31 0.152 0 / 20 2 / 20 8 / 20 32 0.091 0 / 20 0 / 20 2 / 20 33 0.048 0 / 20 0 / 20 0 / 20 4 0.020 0 / 20 0 / 20 0 / 20
[0221] [Table 9]
[0222]
[0223] [Table 10]
[0224]
[0225] [Table 11]
[0226]
[0227] [Table 12]
[0228]
[0229] [Table 13]
[0230]
[0231] According to Tables 1 and 2, it can be confirmed that the results of the 320°C thermal shock test are good when the dielectric composition has Ba-Mg-Si-O segregation particles (sample numbers 4 to 6) compared to the case where the dielectric composition does not have Ba-Mg-Si-O segregation particles (sample numbers 1 to 3).
[0232] According to Tables 3 and 4, it can be confirmed that the results of the 350°C thermal shock test are good when the ratio of Mg to the total of Mg and Si in the Ba-Mg-Si-O segregated particles is 0.25 to 0.75 (sample numbers 13, 4 and 14), compared to the case where the ratio of Mg in the Ba-Mg-Si-O segregated particles to the total of Mg and Si deviates from 0.25 to 0.75 (sample numbers 12 and 15).
Claims
1. A dielectric composition, wherein: The dielectric composition comprises main phase particles and segregation particles, At least a portion of the segregated particles are Ba-Mg-Si-O segregated particles containing Ba, Mg, Si and O. When the total amount of the metal element and Si in the Ba-Mg-Si-O segregation particles is 100 parts by mole, the total amount of Ba, Mg and Si in the Ba-Mg-Si-O segregation particles is 70 parts by mole or more.
2. The dielectric composition according to claim 1, wherein The Ba—Mg—Si—O segregation particles exist at the grain boundaries of the main phase particles.
3. The dielectric composition according to claim 1, wherein The ratio of Mg in the Ba—Mg—Si—O segregated particles to the total of Mg and Si is 0.25 to 0.
75.
4. The dielectric composition according to claim 1, wherein The average particle size of the Ba—Mg—Si—O segregated particles is less than 0.1 μm.
5. The dielectric composition according to claim 1, wherein In total, 5 μm 2 When the cross section of the dielectric composition is observed, the Ba-Mg-Si-O segregated particles are observed to be 0.5 to 10 particles / μm on average. 2 .
6. The dielectric composition according to claim 1, wherein The main phase particles are composed of BaTiO3.
7. The dielectric composition according to claim 1, wherein The composition of the Ba-Mg-Si-O segregation particles is Ba{Mg a Si (1-a) }4O7, The a is 0.25 to 0.
75.
8. An electronic component, wherein: A dielectric composition according to any one of claims 1 to 7.
Citation Information
Patent Citations
Ceramic capacitor and its manufacture
JP2001006966A
Medium transport device
JP2023133537A